An Overview on Green Technologies (International Journal of Innovative Research in Computer Science & Technology, 2020)
Climate change, energy depletion, global  warming, as well as other worries about the environment  have prompted the development of green technology in  recent years. According to researchers, as the degree of  sustainable development rises, so will the economy and  society. It will also have a significant effect on long-term  sustainability. Human creativity and invention are marked  by technological advances in contemporary civilization.  However, these technologies have wreaked havoc on the  environment on a local, regional, and global scale. Green  technologies have a bright future when it comes to  fulfilling the demands of long-term economic viability.  However, reciprocal reinforcement of environmental and  social sustainability aspects is required. Before a  technology is implemented, its environmental and  economic effect, as well as its efficiency, should be  assessed. When economic and long-term development is strongly prioritized, it should be a win-win scenario. This  article addresses the difficulties of developing and  adopting green technology, as well as the tendencies that  contribute to sustainability. Regulatory regulations and  financial problems are also discussed in the study.
Keywords: Clean Technologies; Green Technologies; Sustainability; Sustainable Development